Heliocentric distance dependence of zodiacal light observed by Hayabusa2# - Kohji Tsumura; Shuji Matsuura; Kei Sano; Takahiro Iwata; Hajime Yano; Kohei Kitazato; Kohji Takimoto; Manabu Yamada; Tomokatsu Morota; Toru Kouyama; Masahiko Hayakawa; Yasuhiro Yokota; et al. (Earth, Planets and Space, 2023)
Abstract Zodiacal light (ZL) is sunlight scattered by interplanetary dust particles (IDPs) at optical wavelengths. The spatial distribution of IDPs in the Solar System may hold an important key to understanding the evolution of the Solar System and material transportation within it. The number density of IDPs can be expressed as $$n(r) \sim r^{-α }$$ n ( r ) ∼ r - α , and the exponent $$α \sim 1.3$$ α ∼ 1.3 was obtained by previous observations from interplanetary space by Helios 1/2 and Pioneer 10/11 in the 1970s and 1980s. However, no direct measurements of $$α $$ α based on ZL observations from interplanetary space outside Earth’s orbit have been performed since then. Here, we introduce initial results for the radial profile of the ZL at optical wavelengths observed over the range 0.76 $$-$$ - 1.06 au by ONC-T aboard the Hayabusa2# mission in 2021-2022. The ZL brightness we obtained is well reproduced by a model brightness, although there is a small excess of the observed ZL brightness over the model brightness at around 0.9 au. The radial power-law index we obtained is $$α = 1.30 ± 0.08$$ α = 1.30 ± 0.08 , which is consistent with previous results based on ZL observations. The dominant source of uncertainty arises from the uncertainty in estimating the diffuse Galactic light (DGL). Graphical Abstract